Profil Berpikir Reflektif Siswa dalam Menyelesaikan Soal AKM Ditinjau dari Adversity Quotient - Daniati, Asti Melina; Khotimah, Rita Pramujiyanti (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to describe the profile of students' reflective thinking in solving AKM problems in terms of adversity quotient level. The method used is qualitative with a descriptive approach with the stages of giving written tests completed with the think-aloud technique, observation of answer sheets, interviews, data reduction, data analysis, data coding, and conclusions. The results showed that: (1) the reflective thinking profile of quitter students in solving AKM problems meets all indicators of the techniques component and one indicator on the conceptualization component, (2) the reflective thinking profile of camper students in solving AKM problems does not meet one indicator on the conceptualization component, namely thinking of other ways to solve problems, (3) the reflective thinking profile of climber students in solving AKM problems meets all components of reflective thinking including techniques, monitoring, insight, and conceptualization. In conclusion, each level of adversity quotient has a different reflective thinking profile according to the criteria of each type.   Keywords: Adversity Quotient, AKM, Reflective Thinking.